Penerapan Model Pembelajaran Kooperatif Tipe STAD Dalam Meningkatkan Hasil Dan Proses Matematika Siswa Kelas V UPTD SD Negeri 3 Parepare - Pasinggi, Yonathan S; Djabba, Rasmi; Juhari, Agusalim; K, Agnes Arnil (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
This research is motivated by the learning outcomes of students who have not reached the SKBM in class V UPTD SD Negeri 3 Parepare. The purpose of this study was to determine the process of applying cooperative learning models of Student Team Achievement Division types in improving the process and learning outcomes of mathematics in data presentation material. The approach used is a qualitative approach and the type of research is classroom action research (CAR). The subjects of this study were teachers and students of class V UPTD SD Negeri 3 Parepare, totaling 15 students consisting of 1 teacher, 8 boys and 6 girls. Data were obtained through observation, test and documentation techniques. The data analysis technique used is qualitative data analysis techniques. The results showed that in the first cycle the results of observations of teacher activities with sufficient qualifications (C) and observations of student activities with sufficient qualifications (C). In the second cycle showed an increase in the results of observations of teacher activities into good qualifications (B) and observations of student activities with good qualifications (B). The conclusion of this study is that by applying the cooperative learning model of Student Team Achievement Division types, it can improve the process and student learning outcomes in data presentation material in class V UPTD SD Negeri 3 Parepare